Uma análise crítica das distorções harmônicas de correntes associadas a aerogeradores DFIG - Lima, Michelly da Silva (2019)
In the context of renewable energy generation schemes, wind farms occupy a prominent position in the composition of the electrical energy matrix of the world scenario and of Brazil. Notwithstanding the attractive features, when integrating these generation complexes into the electric systems in operation, studies of the integration between new and existing facilities are necessary. These issues cover a range of analyses, which aim above all to ensure the operational guarantee of the AC grid in line with the applicable legislation. Among the studies of the correlation between the new accesses and their impacts upon the connection network stand out those related to the Quality of Energy. In this scenario, in light of the recognition that the wind power units are interconnected to the electrical networks through technologies involving electronic inverters, these arrangements undoubtedly culminate in the production and injection of current harmonic components. In order to guarantee acceptable standards of performance, the regulatory bodies define conditions imposed on new accesses, which must be evaluated in the planning stage of the installations. At this early step, performance studies are initially based on databases provided by manufacturers. Such information, duly treated, thus results in the impacts on the harmonic distortions of voltage at the Coupling Point with the pre-existing grid. Although this is the procedure in practice, the fact is that after the commissioning of the installations, values of current measured and associated with site operation of the wind turbines can be quite different from those initially used. Among the several reasons that may justify such differences, the presence of background distortions at the PCC stands out. In this scenario, the present dissertation is focused on a critical analysis between the orders and levels of the harmonic currents actually found in the measurements and those initially associated with the manufacturers' databases. Studies involving traditional analysis made up based on the frequency domain techniques, corroborated with performance evaluations in the time domain are use to support the analyses made.